Risk factors associated with failures of Varroa treatments in honey bee colonies without broodless period - Giacobino, Agostina; Molineri, Ana Inés; Bulacio Cagnolo, Natalia Veronica; Merke, Julieta; Orellano, Emanuel; Bertozzi, Ezequiel; Masciangelo, German Oscar; Pietronave, Hernan Pablo; Pacini, Adriana Cecilia; Salto, Cesar Eduardo; Signorini, Marcelo (2018)
The treatment against Varroa destructor has become a basic tool in beekeeping practices, mainly during autumn. The treatment effectiveness should be improved by identifying variables affecting the final outcome. The aim of this study was to identify the risk factors associated with the treatment outcome achieved during autumn control of Varroa destructor. The mite infestation after treatment was evaluated in 62 apiaries and data regarding management practices were collected by means of a questionnaire. A mixed-effects model was constructed to associate management variables with the risk of treatment failure occurrence. Colonies with high mite levels prior to treatment (P = 0.002) and owned by beekeepers who did not frequently replace queens (P = 0.001) were associated with a higher risk of treatment failure. Other beekeeping practices indirectly improved treatment effectiveness. An integrated strategy for controlling mites that includes chemotherapy and suitable beekeepers management is needed to keep mite populations low during winter.